Perception Of China Made Cosmetics On Malaysian Consumers - Visaudaran, Shree Kumareshan (2008)
This study on perception of China made cosmetic products on Malaysian consumers has been conducted. This is because in near future most of the cosmetic products will be imported from China, and if this would happen what would be Malaysian Consumer's reaction towards the China made Cosmetic Products.